2022
DOI: 10.1007/s10067-022-06228-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender and sex on diagnosis, treatment outcomes and health-related quality of life in patients with axial spondyloarthritis

Abstract: Axial spondyloarthritis (axSpA) is a chronic inflammatory rheumatic condition, historically considered a predominantly male disease. However, increasing evidence suggests a more equal prevalence between men and women. Of the limited research conducted to date, it is apparent that gender differences exist in terms of time to diagnosis, treatment outcomes and health-related quality of life (HRQoL). Despite this, women are underrepresented in clinical trials and most studies do not stratify by gender to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In fact, they have been used and validated to some extent in pSpA and PsA studies 40–43. It would have been relevant to assess treatment effectiveness; in this sense, although there is some evidence that female patients with axSpA who receive bDMARD therapy have shown reduced rates of therapeutic response as compared with male patients, there is a need for studies in this regard 44 45. However, the cross-sectional design of this study does not allow to assess properly treatment effectiveness and the use of outcomes for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, they have been used and validated to some extent in pSpA and PsA studies 40–43. It would have been relevant to assess treatment effectiveness; in this sense, although there is some evidence that female patients with axSpA who receive bDMARD therapy have shown reduced rates of therapeutic response as compared with male patients, there is a need for studies in this regard 44 45. However, the cross-sectional design of this study does not allow to assess properly treatment effectiveness and the use of outcomes for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Personalised care was intertwined throughout the Rheumacensus programme, with consensus statements and further insights acknowledging the need to consider holistic treatment based on patient phenotype, gender, and socio-economic factors within axSpA care. Similarly, research by Marzo-Ortega et al [ 10 ] revealed gender disparities that exist in terms of representation in clinical research, time to diagnosis, treatment outcomes and HR-QoL. Contributing factors included poor awareness of gender differences in disease manifestation, reported pain, historical biases that axSpA is a male disease and social factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Contributing factors included poor awareness of gender differences in disease manifestation, reported pain, historical biases that axSpA is a male disease and social factors (e.g. employment, marital status) [ 8 , 10 , 21 ]. Consequently, women experience frequent misdiagnosis and diagnostic delay compared with men, leading to detrimental impacts on HR-QoL and psychological health [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory immune-mediated conditions can affect spinal tissues especially support tissues such as ligaments and their entheses of the axial skeleton ( Alber et al, 2022 ; Li et al, 2022 ). Long considered mainly a disease of men, particularly ankylosing spondylitis, has more recently been reported to also affect a subset of females ( Masi, 1992 ; Wright et al, 2020 ; Cunha et al, 2022 ; Marzo-Ortega et al, 2022 ; Stovall et al, 2022 ). Sex differences in disease presentation characteristics ( Chimenti et al, 2021 ), as well as disease activity compared to males have been reported, with females exhibiting higher disease activity than males and exhibiting different response patterns to clinical interventions ( Mease et al, 2021 ; Stovall et al, 2022 ; van der Horst-Bruinsma et al, 2022 ).…”
Section: Influence Of Sex On Msk Tissues As An Adultmentioning
confidence: 99%